Natural and artificial interaction. Symbiotic processes between science, art and design - Federica Dal Falco; Rosanna Veneziano; Michela Carlomagno (Agathón)
The contribution will focus on how the concept of ‘living’ in the contemporary vision of design, with regard to vegetation, influences design culture, a concept constantly faced with the environmental context through practices of imitation of the logic of natural world interpretation of its evolutionary dynamics, the transformation of its elements and, more recently, with activities that investigate the fragile relationship and coexistence with man, to raise awareness of conscious behaviour. The interpretation of the projects will highlight the visions of contemporary design on the links between the anthropic world and the plant and animal world and will investigate design scenarios aimed at prefiguring possible worlds. Critical reflections will connect to the interdisciplinary New European Bauhaus initiative, which contemplates new synergies between natural and cultural, social inclusion, science and technology.